Sustainability Reporting in Fishing Industry Management - Regulation versus Voluntarism - Susan Wild (Australasian Accounting, Business and Finance Journal, 2008)
A growing number of major corporations and industry organizations now overtly advocate the general concept of corporate social and environmental responsibility, commonly emphasising the ‘business case’ for such behaviour on the basis that it is ‘good for business’. Many now report to their stakeholders on a voluntaristic basis a range of information regarding their impacts on the social and physical environment in which they operate. Intrinsic to the business case model is the argument that an optimal balance between the needs of economic growth and the sustainable management of natural resources can best be attained through the conventional mechanisms of corporate governance and voluntary corporate activity, rather than by imposition of governmental regulation. This view implies, however, that where the exigencies of environmental sustainability conflict with those of economic imperatives, the latter must take precedence. A view oppositional to that of the business case instead promotes an intensified interventionist approach towards natural resource management, advocating increased governmental regulation and control, including the mandating, standardization and independent verification of corporate sustainability reporting. This view gives precedence to public good concepts of natural resource management, prioritising intra- and inter-generational equity and human rights theories as to natural resource distribution, and challenges traditional economic approaches to the relational intersects of business, politics and environment science. This paper considers the relative claims for efficacy in achieving desirable corporate environmental behaviours of the business case and voluntary self-regulation model, vis-à-vis those for extended mandatory governmental control, utilizing the exemplar of voluntary sustainability reporting in the New Zealand fishing industry.
Keywords: sustainability reporting; fishing industry; corporate social responsibility